Odpowiedź :
Odpowiedź:
[tex]a)\\\\2x^2-x-3>0\\\\\Delta=b^2-4ac=(-1)^2-4*2*(-3)=1+24=25\\\\\sqrt{\Delta}=\sqrt{25}=5\\\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-5}{2*2}=\frac{1-5}{4}=\frac{-4}{4}=-1\\\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+5}{2*2}=\frac{1+5}{4}=\frac{6}{4}=\frac{3}{2}=1\frac{1}{2}[/tex]
[tex]b)\\\\-x^2+9<0\\\\-x^2<-9\ \ /*(-1)\\\\x^2<9\\\\x=\sqrt{9}\ \ \ \ \vee\ \ \ \ x=-\sqrt{9}\\\\x=3\ \ \ \ \ \ \vee\ \ \ \ x=-3[/tex]
![Zobacz obrazek Magda](https://pl-static.z-dn.net/files/dd4/7e6d4f2d11e294f4ef63a1c0541d8790.jpg)